Demonstration of infective endocarditis by cardiac CT and transoesophageal echocardiography: comparison with intra-operative findings. (23rd February 2017) - Koo, Hyun Jung; Yang, Dong Hyun; Kang, Joon-Won; Lee, Joo Yeon; Kim, Dae-Hee; Song, Jong-Min; Kang, Duk-Hyun; Song, Jae-Kwan; Kim, Joon Bum; Jung, Sung-Ho; Choo, Suk Jung; Chung, Cheol Hyun; et al.
Abstract: Aims: We aimed to compare imaging findings of infective endocarditis between computed tomography (CT) and transoesophageal echocardiography (TEE) using surgical inspection as a reference standard. Methods and results: Forty-nine patients (aged 54 ± 17 years, 69% men) who underwent pre-operative CT and TEE for infective endocarditis were included. Twelve of these patients had prosthetic valve endocarditis. Imaging findings of infective endocarditis were classified as vegetation, leaflet perforation, abscess/pseudoaneurysm, and paravalvular leakage. Diagnostic performances of CT and TEE were evaluated using surgical inspection as a reference standard. Interobserver agreements for CT findings were obtained using Cohen's κ test. The detection rates of infective endocarditis per patient with CT and TEE were 93.9% (46/49) and 95.9% (47/49), respectively. In per-imaging analysis, the sensitivities of CT and TEE were not significantly different for both native and prosthetic valve infective endocarditis (sensitivity: vegetation, 100% in TEE and 90.9% in CT; leaflet perforation, 87.5% in TEE and 50.0% in CT; abscess/pseudoaneurysm, 40.0% in TEE and 60.0% in CT; paravalvular leakage, 100% in TEE and 50.0% in CT). Interobserver agreements for CT findings were substantial or excellent (0.79–0.88). Conclusion: Cardiac CT can accurately demonstrate infective endocarditis in pre-operative patients with a similar diagnostic accuracy to TEE. The interobserver agreements for the CT findings of infective endocarditis were excellent.